The Perceived Demand Curve in the Theory of Second Best - Negishi, Takashi (Review of Economic Studies, 1967)
Journal Article The Perceived Demand Curve in the Theory of Second Best Get access Takashi Negishi Takashi Negishi University of Tokyo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 34, Issue 3, July 1967, Pages 315–316, https://doi.org/10.2307/2296679 Published: 01 July 1967